Improving Innovative Work Behavior Through Creativity and Proactive Personality: A Meta-Analysis - Sulistiasih, Sulistiasih; Pratiwi, Yu Arini Wahyu; Hutahaen, Erik Saut H. (Guidance : Jurnal Bimbingan dan Konseling, 2025)
Innovative work behavior not only plays a critical role in achieving teacher performance and school goals but can also be used to anticipate various new problems for which solutions are not yet available. Therefore, this study is concerned with uncovering the influence of creativity and proactive personality on innovative work behavior (IWB). Empirically, several previous studies suggest that both creativity and proactive personality significantly impact IWB. However, a comprehensive synthesis of empirical findings is needed to clarify the strength and consistency of these relationships. This study employed a quantitative meta-analysis to examine the effects of creativity and proactive personality on IWB. All research’s data published between 2019 and 2025 were regularly selected from Scopus, SINTA, and Google Scholar databases. Using JASP version 0.8.4.0, effect sizes were calculated, and heterogeneity was assessed through a random-effects model. The analysis revealed that creativity and proactive personality significantly impact IWB. Moderate heterogeneity was observed across the studies, and no evidence of publication bias was found. These findings align with existing literature, emphasizing the critical role of creativity and proactive personality in improving IWB. The moderate heterogeneity suggests variability in study contexts, yet the overall effect remains robust. The results highlight the value of creativity and proactive personality in driving teachers' IWB in schools. Practical recommendations include the development of creativity and a proactive personality to improve teachers' IWB.